2022
DOI: 10.3390/ijms23137294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Expression of Coding and Noncoding RNAs in Murine Neuroblastoma Neuro2a Cells

Abstract: Excessive use of alcohol can induce neurobiological and neuropathological alterations in the brain, including the hippocampus and forebrain, through changes in neurotransmitter systems, hormonal systems, and neuroimmune processes. We aimed to investigate the effects of ethanol on the expression of coding and noncoding RNAs in a brain-derived cell line exposed to ethanol. After exposing Neuro2a cells, a neuroblastoma cell line, to ethanol for 24 and 72 h, we observed cell proliferation and analyzed up- and down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This is higher than the average blood alcohol concentration in alcoholdependent subjects. Moreover, it has been reported that in vitro alcohol treatment using concentrations above 100 mmol/L has a direct cytotoxic effect of alcohol on cells [28]. On the other hand, several recent studies could not confirm this observation [29][30][31].…”
Section: Discussionmentioning
confidence: 94%
“…This is higher than the average blood alcohol concentration in alcoholdependent subjects. Moreover, it has been reported that in vitro alcohol treatment using concentrations above 100 mmol/L has a direct cytotoxic effect of alcohol on cells [28]. On the other hand, several recent studies could not confirm this observation [29][30][31].…”
Section: Discussionmentioning
confidence: 94%
“…1 d). Some studies have reported that ethanol could induce changes of lncRNA levels in cells [ 17 19 ], so we constructed a cell model of ethanol treatment to observe whether ethanol can cause changes of lnc171 levels in HCC cells. Before establishing the cell model, we treated cells with gradient concentration of ethanol and measured cellular activity at 24 h, 48 h, and 72 h after ethanol treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol can induce liver damage and hepatic steatosis these lesions can cause alcoholic liver disease to progress to cirrhosis and eventually to HCC [ 35 ]. Ethanol has been proved to be a teratogenic agent and epigenetic regulator that regulates cell biological traits and functions by regulating the expression levels of multiple factors, leading to aggravating liver damage and accelerating the process of liver lesions [ 17 19 ]. In our study, we found that the stimulation of ethanol could increase the expression of lnc171 in HCC cells, and the migration and invasion ability of HCC cells was enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation